Financial Performance Analysis of State-Owned and Private Banks Based on the CAMEL Ratio (2023–2025) - Winda Pretty Handayani Sihombing; Patrisia Patrisia Retnagafia Manao; Christo Randzio Simbolon; Nurhafifah Amalina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze and compare the financial performance of state-owned and private banks in Indonesia using the Capital, Asset Quality, Management, Earnings, and Liquidity (CAMEL) framework during the 2023–2025 period. A quantitative descriptive approach with a comparative study design was employed based on the analysis of annual reports and financial statements of PT Bank Mandiri (Persero) Tbk., PT Bank Negara Indonesia (Persero) Tbk., PT Bank Central Asia Tbk., and PT Bank CIMB Niaga Tbk. The data were analyzed using CAMEL ratios, including the Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Expenses to Operating Income Ratio (BOPO), Return on Assets (ROA), Return on Equity (ROE), and Loan-to-Deposit Ratio (LDR). The findings indicate that all sampled banks were classified as financially sound in accordance with the standards established by Indonesia's Financial Services Authority. Among the private banks, PT Bank Central Asia Tbk. demonstrated superior performance in terms of capital adequacy, profitability, and operational efficiency, as reflected by its high CAR, ROA, and ROE values and low BOPO ratio. Meanwhile, among the state-owned banks, PT Bank Mandiri (Persero) Tbk. exhibited the strongest performance in maintaining asset quality, as indicated by the lowest NPL ratio, while also demonstrating an effective intermediary function through its lending activities. The study confirms that the CAMEL framework remains a relevant and effective tool for evaluating and comparing bank soundness and can provide valuable insights for bank management, investors, and regulators in strategic decision-making.